Photoresponsive surface molecularly imprinted poly(ether sulfone) microfibers - Wang, Dongsheng (Langmuir : the ACS journal of surfaces and colloids, 2012)
In the present study, photoresponsive surface molecularly imprinted poly(ether sulfone) microfibers are prepared via nitration reaction, the wet-spinning technique, surface nitro reduction reaction, and surface diazotation reaction for the selectively photoregulated uptake and release of 4-hydrobenzoic acid. The prepared molecularly imprinted microfibers show selective binding to 4-HA under irradiation at 450 nm and release under irradiation at 365 nm. The simple, convenient, effective, and productive method for the preparation of azo-containing photoresponsive material is also applied to the modification of polysulfone and poly(ether ether ketone). All three benzene-ring-containing polymers show significant photoresponsibility after the azo modification